Biotechnological approaches to enhance biofuel producing potential of microalgae. (15th October 2021) - Xue, Jiao; Balamurugan, Srinivasan; Li, Tong; Cai, Jia-Xi; Chen, Ting-Ting; Wang, Xiang; Yang, Wei-Dong; Li, Hong-Ye
Highlights: Genetic improvement of microalgae is demanded to enhance algal productivity. Potential regulatory node of metabolic network is pivotal for genetic improvement. Significance of streamlining algal genetic engineering approaches is emphasized. Commercial associated combinatorial strategy is proposed for algal industry. Abstract: Oleaginous microalgae have emerged as the promising feedstock for biofuels due to their various advantageous features over terrestrial plants. However, the microalgal fuel industry is still in its infancy due to the unavailability of robust algal strains with enhanced lipid content and biomass and economically feasible oil extraction strategies. Microalgal metabolic engineering shows the great potential to enhance lipid accumulation without impairing cell growth by targeted control of key metabolic nodes. Despite the recent advancements in synthetic biology, genetic improvement of microalgae without hindered cellular biomass remains an untapped tool for large-scale biofuel production. In this review, we therefore provide a comprehensive overview of various metabolic engineering strategies for lipid enhancement and the necessity of designing the appropriate strategy for scale-up processes. We have emphasized the need of streamlining the engineering strategies with the aid of recent advancements in DNA manipulation techniques to obviate the existing biological intricacies in lipogenesis. We outline the significance of recruiting potential engineering strategies such as transcription engineering, heterologous recombineering, and genome engineering to generate chassis algal strains successfully. Besides, this review highlights the designing of modular strategies by subjecting the engineered strains under sub-optimal conditions, mixotrophic cultivations and chemical treatment to overcome the existing bottlenecks in microalgal commercialization. This review also discusses the current large-scale algal cultivation units and the drawbacks. Overall, this review provides insights into employing the metabolic rewiring strategies to engineer the intricate lipogenic circuit in microalgae for enhancing biofuel potential.